Formate Oxidase (FOx) from Aspergillus oryzae: One Catalyst Enables Diverse H(2)O(2)‐Dependent Biocatalytic Oxidation Reactions - Tieves, Florian (Angew Chem Int Ed Engl, 2019)
An increasing number of biocatalytic oxidation reactions rely on H(2)O(2) as a clean oxidant. The poor robustness of most enzymes towards H(2)O(2), however, necessitates more efficient systems for in situ H(2)O(2) generation. In analogy to the well‐known formate dehydrogenase to promote NADH‐dependent reactions, we here propose employing formate oxidase (FOx) to promote H(2)O(2)‐dependent enzymatic oxidation reactions. Even under non‐optimised conditions, high turnover numbers for coupled FOx/peroxygenase catalysis were achieved.